Analisisa Pengendalian Risiko Kecelakaan Kerja Pada Area Produksi Menggunakan Metode Hazard Identification Risk Assesment and Risk Control (HIRARC) di PT Fahifa Prima Mandiri - Naufal Muhammad Rafi Fauzan; Kusnadi Kusnadi (Peneliti.net, 2022)
Research conducted at PT Fahifa Prima Mandiri in the production area, with the aim of identifying potential hazards and risks of work accidents, analyzing potential hazards and risks, as well as efforts to control and prevent occupational accident risks using the HIRARC (hazard identification, risk assessment, and risk assessment) method. controls). The data used in this study is to use primary data and secondary data. Data analysis and discussion using qualitative and descriptive data. The results of the analysis of the potential hazard analysis found as many as 30 potential hazards including 18 low risk, 5 moderate risk, 5 high risk, and 2 extreme risks. proposed controls to reduce the possibility of work accidents that occur are the addition of protective covers on grinding machines, adding foot switches on bandsaw, milling, and lathe machines, carrying out 5R activities, using PPE such as (safety shoes, safety gloves, safety glasses, and respirators or masks), adding fire extinguishers and first aid kits